Nucleotide sequence analysis of the hypervariable region III of mitochondrial DNA in Thais - Thongngam P. (2017)
© 2016 Elsevier Ltd and Faculty of Forensic and Legal Medicine. All rights reserved. This study analyzed the nucleotide sequences of the hypervariable region III (HVRIII) of mitochondrial DNA in Thai individuals. Buccal swab samples were randomly obtained from 100 healthy, unrelated, adult (18-60 years old), volunteer donors living in Thailand. Eighteen different haplotypes were found, of which 11 haplotypes were unique. The most frequent haplotypes observed were 522D-523D. Nucleotide transition from Thymine (T) to Cytosine (C) at position 489 (43%) was the most frequent substitution. Nucleotide transversions were also observed at position 433 (Adenine (A) to C, 1%) and position 499 (Guanine (G) to C, 1%). Fifty-three samples presented nucleotide insertion and deletion of C and A (CA) at position 514-523. Insertion of 1AC (3%) and 2AC (2%) were observed. Deletion of 1CA (53%) and 2CA (2%) at position 514-523 were revealed. The deletion of T at position 459 was observed. The haplotype diversity, random match probability, and discrimination power were calculated to be 0.7770, 0.2308, and 0.7692, respectively.